Select aspects of oogenesis and folliculogenesis - Grygoruk, Cezary; Sieczyński, Piotr; Ratomski, Karol; Grusza, Mirosław; Mrugacz, Grzegorz (Medical Studies/Studia Medyczne, 2013)
The processes of oogenesis and folliculogenesis begin very early in foetal life and are continued until the end of the reproductive period. Despite the numerous research conducted, the mechanism which initiates the growth of primary follicles has not been fully elucidated. The process of oocyte maturation begins after the recruitment of the primary follicle and continues until ovulation. This involves synthesis and accumulation of an appropriate number and kind of compounds and redistribution of cellular organelles inside the oocyte, which are necessary for the processes of fertilization and early embryonic development. The complexity and multi-functionality of these mechanisms and the factors which take part in the process of oogenesis indicate a necessity to conduct further research concerning this issue. A more thorough understanding of the processes of oogenesis and folliculogenesis will allow in time to develop more effective methods of treatment for a range of gynaecological, oncological, and endocrinological disorders.